Stormy relations between Kiev and Moscow: Conflict over energy policy and external security - Rainer Lindner (Stiftung Wissenschaft und Politik (SWP), 2008)
Conflicts over gas supplies and Kiev's overtures to NATO are currently placing great strain on relations between Ukraine and Russia. The energy compromise reached in mid-March will not last beyond the end of this year, and Moscow will continue to oppose any plans to integrate Ukraine in the western alliances of NATO and the EU, arguing that this move would disrupt Europe's security architecture. And the Ukrainian political class is divided, with energetic opposition protests against the government's plans to join NATO paralyzing parliament for weeks. Energy policy and Ukraine's geopolitical orientation are the central conflicts in Ukrainian-Russian relations, with considerable repercussions on the member states of NATO and the EU. Both organizations should intensify and interlink their cooperation with Moscow and Kiev
Keywords: 320